Syntheses, reactivity, and biological applications of coumarins - Citarella, Andrea; Vittorio, Serena; Dank, Christian; Ielo, Laura (Frontiers in Chemistry, 2024)
This comprehensive review, covering 2021-2023, explores the multifaceted chemical and pharmacological potential of coumarins, emphasizing their significance as versatile natural derivatives in medicinal chemistry. The synthesis and functionalization of coumarins have advanced with innovative strategies. This enabled the incorporation of diverse functional fragments or the construction of supplementary cyclic architectures, thereby the biological and physico-chemical properties of the compounds obtained were enhanced. The unique chemical structure of coumarine facilitates binding to various targets through hydrophobic, pi-stacking, hydrogen bonding, and dipole-dipole interactions. Therefore, this important scaffold exhibits promising applications in uncountable fields of medicinal chemistry (e.g. neurodegenerative diseases, cancer, inflammation).